Decision-making Processes for a Patient Admitted to the Accident and Emergency Department Requiring Emergency Abdominal X-ray ? A Case Study - Y. Yuliawati (ASEAN Journal on Science and Technology for Development, 2016)
This study investigated the application of the various processes involved in decision-making for acase requiring radiologic emergency abdominal X-ray examination to the Accident and Emergency Department in a government-owned hospital in West Java, Indonesia. It is also aimed to evaluate the patient who was experiencing abdominal pain accompanied by bloating, vomiting, severe constipation and abdominal cramps.The decision-making models used for this case were the normative, prescriptive and descriptive judgments. A decision tree in the form of decision options that was employed in this case addressed the normative model of decision-making, while the algorithm and information processing theory focused on the prescriptive model. Lastly, the intuition that was used in this case concentrated on the descriptive model of decision-making. An emergency abdominal X-ray was indicated for the patient ? a prescriptive decision. Options from decision trees were also practiced. However, the patient was in pain; therefore, she was unable to understand the alternatives that were presented. Hence, this choice was suggested by the author because, by intuition, the expectation was that the patient suffered from acute abdominal crisis.